Motor Nonlinearities in Electrodynamic Loudspeakers: Modelling and Measurement - Benoit MERIT; Valérie LEMARQUAND; Guy LEMARQUAND; Andrzej DOBRUCKI (Archives of Acoustics)
This paper studies the motor nonlinearities of a classical electrodynamic loudspeaker. Measurements show the dependence of the voice-coil inductance with its position and with the driving current as well as the force factor dependence on the coil position. They allow the tuning of the parameters of a model proposed for these dependences. Time and frequency analysis of the model help in the explanation of both the harmonic and intermodulation distortions observed in classical loudspeakers.